Pseudoaneurysm in the Internal Maxillary Artery Occurring After Endoscopic Sinus Surgery - Lee, Eun Jung (J Craniofac Surg, 2016)
Pseudoaneurysm is defined as blood leaking out of a vessel that does not have true 3 arterial walls like a true aneurysm, and is susceptible to rupture. Only 4 patients of pseudoaneurysm after endoscopic sinus surgery have been reported so far in English literature. Recently, the authors encountered a pseudoaneurysm in the internal maxillary artery after endoscopic sinus surgery, which was immediately and successfully managed with endovascular embolization. There was no bleeding or complications 6 months after the embolization.